Sex Work, Essential Work: A Historical and (Necro)Political Analysis of Sex Work in Times of COVID-19 in Brazil - Betania Santos; Indianarae Siqueira; Cristiane Oliveira; Laura Murray; Thaddeus Blanchette; Carolina Bonomi; Ana Paula da Silva; Soraya Simões (Social Sciences, 2020)
Brazil has made international headlines for the government’s inept and irresponsible response to the COVID-19 pandemic. In this context, sex worker activists have once again taken on an essential role in responding to the pandemic amidst State absences and abuses. Drawing on the theoretical framework of necropolitics, we trace the gendered, sexualized, and racialized dimensions of how prostitution and work have been (un)governed in Brazil and how this has framed sex worker activists’ responses to COVID-19. As a group of scholars and sex worker activists based in Rio de Janeiro and São Paulo, we specifically explore the idea of sex workers as “essential workers”, but also of sex work as, essentially, work, demonstrating complicities, differences, and congruencies in how sex workers see what they do and who their allies in the context of the 21st century’s greatest health crisis to date.